Genotype–phenotype characteristics of Vietnamese patients diagnosed with Charcot–Marie–Tooth disease. Issue 9 (8th August 2022) - Nguyen‐Le, Trung‐Hieu; Do, Minh Duc; Le, Linh Hoang Gia; Nhat, Quynh Nhu Nguyen; Hoang, Nghia Trong Tien; Van Le, Tuan; Mai, Thao Phuong
Abstract: Background: Charcot–Marie‐Tooth (CMT) disease is one of the most common hereditary neuropathies. Identifying causative mutations in CMT is essential as it provides important information for genetic diagnosis and counseling. However, genetic information of Vietnamese patients diagnosed with CMT is currently not available. Methods: In this study, we described the clinical profile and determined the mutation spectrum of CMT in a cohort of Vietnamese patients with CMT by using a combination of multiplex ligation‐dependent probe amplification and next‐generation sequencing targeting 11 genes PMP22, MPZ, EGR2, NEFL, MFN2, GDAP1, GARS, MTMR2, GJB1, RAB7A, LITAF . Results: In 31 CMT cases, the mutation detection rate was 42% and the most common genetic aberration was PMP22 duplication. The pedigree analysis showed two de novo mutations c.64C > A (p.P22T) and c.281delG (p.G94Afs*17) in the NEFL and PMP22 genes, respectively. Conclusion: The results of this study once again emphasize the important role of molecular diagnosis and provide preliminary genetic data on Vietnamese patients with CMT. Graphical Abstract: